PROSES KREATIF PENCIPTAAN TARI RINYUAKNG OLEH GABRIEL ARMANDO - Mardianti, Desti; Satrianingsih, Aline Rizky Oktaviari; Oktariani, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to find out the creative process of the creation of the Rinyuakng dance by Gabriel Armando and describe the choreographic form of the dance. This form of research uses qualitative and descriptive research methods with a choreographic approach. The collection of research data uses interviews with resource persons, observation and documentation studies. The technique used to test the validity of the data by extended observation and source triangulation. Gabriel Armando's creative process of creating the Rinyuankg Dance departed from the need to fulfill the final assignment at the ISI Yogyakarta Postgraduate School in 2010 which was the first regional son to carry out his final assignment in West Kalimantan. This dance work is also a form of Gabriel's response to the importance of Rinyuakng in the traditional ceremonies of the Dayak Kanayatn community. Based on the results of the research, internal factors that come from oneself and external such as family, work, and society influenced Gabriel Armando when creating the Rinyuakng Dance. The result of the creative process of the Rinyuakng Dance is a work with the theme of the myth of Rinyuakng leaves which has the order of life and customs, customs and guidelines of the Dayak Kanayatn community as part of culture.